2022
DOI: 10.1007/s11274-022-03243-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mannosylerythritol lipid-B components in antimicrobial activity against bovine mastitis-causing Staphylococcus aureus

Abstract: Mannosylerythritol lipid-B (MEL-B), which comprises ester-bonded hydrophilic ME and hydrophobic fatty acids, is a bio-surfactant with various unique properties, including antimicrobial activity against most gram-positive bacteria. The gram-positive Staphylococcus aureus is a causative pathogen of dairy cattle mastitis, which results in considerable economic loss in the dairy industry. Here, we demonstrate the efficacy of MEL-B as a disinfectant against bovine-derived S. aureus and elucidate a mechanism of acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The researchers concluded that MELs exhibit a robust inhibitory effect on Gram-positive bacteria, along with some sensitivity towards Pseudomonas strains. Antimicrobial activity was further studied in the food-borne pathogens S. aureus, Bacillus cereus and Listeria monocytogenes [35][36][37][38]78]. It was observed that MELs' antimicrobial effect was linked to their capacity to damage the integrity of cell membranes.…”
Section: Biomedical/pharmaceutical Industriesmentioning
confidence: 99%
“…The researchers concluded that MELs exhibit a robust inhibitory effect on Gram-positive bacteria, along with some sensitivity towards Pseudomonas strains. Antimicrobial activity was further studied in the food-borne pathogens S. aureus, Bacillus cereus and Listeria monocytogenes [35][36][37][38]78]. It was observed that MELs' antimicrobial effect was linked to their capacity to damage the integrity of cell membranes.…”
Section: Biomedical/pharmaceutical Industriesmentioning
confidence: 99%
“…The researchers concluded that MELs exhibit a robust inhibitory effect on grampositive bacteria, along with some sensitivity from the Pseudomonas strains. The antimicrobial activity was further studied in the food-borne pathogens S. aureus, Bacillus cereus and Listeria monocytogenes [28][29][30][31]68]. It was observed that MELs antimicrobial effect is linked to its capacity to damage the integrity of cell membranes.…”
Section: Biomedical/pharmaceutical Industrymentioning
confidence: 99%
“…A MEL-B biosurfactant obtained from P. tsukubaensis NBRC1940 acted as a disinfectant agent, inducing inhibition of cell growth of dairy cattle mastitis agents S. aureus, with its activity being correlated with the transportation of fatty acids (caprylic acid and myristoleic acid) with antimicrobial activity to the surface of bacterial cells [187]. On the contrary, the biosurfactant had no effect against Gram-negative bacteria E. coli, although it bounds on the surface of the cell.…”
Section: Mannosylerytrithol Lipids For Biomedical Usementioning
confidence: 99%